Separability and subadditivity in Australian railways - Wills-Johnson, Nick (Blackwell Publishing, 2008)
Economic reform in the mid-1990s saw the application of third-party access to railway infrastructure and, in some cases, the separation of above-rail and below-rail services into separate businesses. Reform was based on the notion that the rail track was a natural monopoly, while the above-rail sector could potentially support competition. This paper examines the likelihood of such competition through an analysis of subadditivity, and also the consequences of vertical separation for rail efficiency. It finds limited evidence for sustainable above-rail competition, but also limited evidence that vertical separation should have caused efficiency losses.